(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article is devoted to the jadid movement went through hard times in a historical multi-faceted way. Jadidism became the arena of struggle of various philosophies and worldly methods of approach to perspectives of social development. It focused on key questions about social development: the conceptual sense of the ideology of breaking the basic foundations of feudalism and colonialism.